Ultrafast Sodium Full Batteries Derived from XFe (X = Co, Ni, Mn) Prussian Blue Analogs. Issue 3 (14th November 2018) - Ge, Peng; Li, Sijie; Shuai, Honglei; Xu, Wei; Tian, Ye; Yang, Li; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Exploring high‐rate electrode materials with excellent kinetic properties is imperative for advanced sodium‐storage systems. Herein, novel cubic‐like XFe (X = Co, Ni, Mn) Prussian blue analogs (PBAs), as cathodes materials, are obtained through as‐tuned ionic bonding, delivering improved crystallinity and homogeneous particles size. As expected, Ni‐Fe PBAs show a capacity of 81 mAh g −1 at 1.0 A g −1, mainly resulting from their physical–chemical stability, fast kinetics, and "zero‐strain" insertion characteristics. Considering that the combination of elements incorporated with carbon may increase the rate of ion transfer and improve the lifetime of cycling stability, they are expected to derive binary metal‐selenide/nitrogen‐doped carbon as anodes. Among them, binary Ni0.67 Fe0.33 Se2 coming from Ni‐Fe PBAs shows obvious core–shell structure in a dual‐carbon matrix, leading to enhanced electron interactions, electrochemical activity, and "metal‐like" conductivity, which could retain an ultralong‐term stability of 375 mAh g −1 after 10 000 loops even at 10.0 A g −1 . The corresponding full‐cell Ni‐Fe PBAs versus Ni0.67 Fe0.33 Se2 deliver a remarkable Na‐storage capacity of 302.2 mAh g −1 at 1.0 A g −1 . The rational strategy is anticipated to offer more possibilities for designing advanced electrode materials used in high‐performance sodium‐ion batteries. Abstract : Cubic‐like X Fe (X = Co, Ni, Mn) Prussian blue analogs (PBAs) are designed through as‐tuned ionic bonding of XFe. Ni‐Fe PBAs as cathode show "zero‐strain" insertion traits with physical–chemical stability, and their derived binary metal‐selenide as anode displays strong metal‐like conductivity. Their matched sodium full‐cell systems deliver reasonably high and fast specific capacity.